Comparison between Combined Spinal and General Anaesthesia versus General Anaesthesia Alone for Laparoscopic Gynaecological Procedures: A Randomised Controlled Study - Bhavini Shah; Pragya Pramanik; Brinda Badam; Reshma Salim (Journal of Clinical and Diagnostic Research)
Introduction: Laparoscopic gynaecological surgery provides less surgical trauma, shorter recovery, and less postoperative pain. Although General Anaesthesia (GA) is widely used, adding Spinal Anaesthesia (SA) to GA can give better haemodynamic stability and better perioperative outcomes. The current study contrasts SA and GA combination (SGA) with GA alone in laparoscopic gynaecological surgery. Aim: To compare and assess the impact of SGA versus GA alone on intraoperative haemodynamics, Isoflurane and metoprolol needs, recovery time, satisfaction of the surgeon, and postoperative complications. Materials and Methods: This randomised controlled trial was conducted at Dr. D.Y. Patil Medical College, involving 50 laparoscopic gynaecological surgery patients. Patients were divided randomly into two groups. Group SGA was administered both SA and GA, while group GA was administered GA. Haemodynamic parameters, demand for anaesthetic agents, duration of recovery, and surgeon satisfaction scores (NRS) were measured and examined. Side-effects like hypotension, nausea, and vomiting were also evaluated. The gathered data were compiled, entered into Microsoft Excel, and analysed using Statistical Package for Social Sciences (SPSS) version 27.0 and if data were not normally distributed the Mann-Whitney U test was used. For categorical variables, the Chi-square test or Fisher’s-Exact test was used. Results: Demographics and baseline haemodynamic parameters were similar in both groups. Group GA had significantly more isoflurane requirement (0.728±0.0817) than group SGA (0.36±0.08) (p<0.0001). Intraoperative metoprolol was needed in only group GA (3.86±1.35 mg). Recovery time was significantly less for group SGA (3.94±0.14 min) than for group GA (7.35±1.1 min) (p<0.0001). Surgeon satisfaction was greater in group SGA (7.2±0.82 vs. 4.28±1.1, p<0.0001). Duration of surgery and pneumoperitoneum times were comparable in both groups (p>0.05). Side-effects were minimal. Six patients in group GA had nausea and vomiting, while two in group SGA had hypotension. Conclusion: The use of SA and GA together in laparoscopic gynaecological surgery results in improved intraoperative haemodynamic control, less requirement of anaesthetic drugs, shorter recovery time, and increased surgeon satisfaction without adding side-effects. SGA can be considered a more desirable option than GA alone in selected patients receiving such procedures.